Die Basilius-Übersetzung des Georg von Trapezunt in ihrem historischen Kontext / - Abenstein, Christina (De Gruyter, 2014)
George of Trebizond (1396–1472/3) is among the most colorful figures of early Italian humanism. His translation of the dogmatic works of St. Basil the Great, commissioned by Cardinal Bessarion, should be seen not only in the context of the Unity Council of Ferrara-Florence but also in terms of its singular role in the Plato-Aristotle controversy and in George’s major falling-out with Bessarion.
10.1515/9783110379181
Keywords: Georgius; Literature; Literatur; Rhetorik; Literaturwissenschaft.